2021
DOI: 10.1007/s00227-021-03822-1
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of Lepas-based biofouling communities on moored and drifting objects, with applications for marine forensic science

Abstract: Pelagic biofoulers such as barnacles or bryozoans settle and raft on natural debris like pumice or seeds. Recent influxes of marine debris into the world's oceans, especially plastic, have increased habitat availability for these biofoulers. Goose barnacles in the genus Lepas are some of the most common biofouling taxa globally, and play an important role in biofouling communities as foundation species. We examined community succession, growth rates and isotopic composition in Lepas and their associated biofou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 68 publications
3
30
2
Order By: Relevance
“…Lepas is a common biofouling taxon distributed globally and plays a role in biofouling as a foundation organism [26]. The shell growth rate is more than 1 mm/day in some Lepas species [27]. We found that Lepas on pumice stones had grown in two weeks.…”
Section: Changes In the Coastal Landscape: Natural Beaches And Estuariesmentioning
confidence: 79%
“…Lepas is a common biofouling taxon distributed globally and plays a role in biofouling as a foundation organism [26]. The shell growth rate is more than 1 mm/day in some Lepas species [27]. We found that Lepas on pumice stones had grown in two weeks.…”
Section: Changes In the Coastal Landscape: Natural Beaches And Estuariesmentioning
confidence: 79%
“…Using information on biofouling and degradation state, it is sometimes possible to estimate how long a plastic item has been in the ocean (Mesaglio et al., 2021 ). To investigate how this particle age, defined here as the time the plastic has spent in the ocean from source to final destination, can be used to further narrow the possible sources of plastic found, we have analyzed source probabilities as a function of particle age for any age between 0 and 24 months.…”
Section: Resultsmentioning
confidence: 99%
“…Lepas is a common biofouling taxon distributed globally and plays a role in biofouling as a foundation organism. The shell growth rate is more than 1 mm/day in some Lepas species 32 suggesting that the Lepas had been growing on the pumice for about two weeks. Measurements of the shell size of Lepas attached to the pumice collections conducted in the same area (Supplementary Video 2 ) showed a bias toward larger sizes in the second collection (5.92 ± 3.86 mm (average ± S.D.…”
Section: Resultsmentioning
confidence: 99%